Guidelines for determining the most economical roadway surface type for local rural roads - Patel, Himanshu S. (Kansas State University, 2016)
The percentage of gravel roads in rural areas in Kansas is higher than most states. A wide variation of traffic volumes across different regions and variations of local conditions and scenarios present a great challenge for local agencies to determine suitable roadway surface types for local rural roads, especially considering constraints on transportation budgets. The primary objective of this research was developing specific guidelines to identify the most suitable roadway surface for a particular roadway section with given conditions. Surveys were carried out to determine the importance of factors affecting the selection of a roadway surface type, where were later used for guideline development. General guidelines were developed using the multi-criteria assessment method in order to fulfill the main objective. The main important factors in decision-making were identified as agency cost, safety, Vehicle Operating Cost (VOC), traffic volume, purpose of road usage, and public preference. Multi-criteria assessment method involves calculating the weights for the factors important in decision-making, the respective scaled values for each factor for paved surface and gravel surface, and eventually calculating the final score for paved and gravel surface type. Equations were formulated to carry out life cycle cost (LCC) analysis along with the present worth evaluation. The formulas provided flexibility to calculate agency cost by considering local variation. VOC was calculated for paved and gravel roads considering variations in speed of different classes of vehicles, gradient and horizontal curve of the road, and the conversion factor for cost on paved surface versus gravel surface. Safety analysis was carried out for local rural roads in Kansas for five years, from 2010 to 2014, using the Kansas Department of Transportation’s KCARS database. After calculating the EPDO crash rates on paved and gravel roads in Kansas, results showed that paved surfaces were in general safer than gravel surfaces, which was taken into consideration while calculating the scaled values for safety. The final score was calculated by multiplying the weights of each factor and their respective scaled values. Roadway surface type with higher score is the preferred alternative for a road section under consideration. A computer-based program was created as a user interface, using Visual Studio, to carry out all complex calculations for determining LCC and VOC considering local variations. The program also helped determine final total scores for paved and gravel roads by considering scaled values of all-important factors considered for conversion. Another approach using cost versus traffic volume showed that the break-even point for traffic volume decreased with an increased percentage of trucks and increased vehicle speeds. Thus, the developed guideline helps determine the best roadway surface type for any set of local conditions.
Keywords: Gravel roads; Local rural roads; Multicriteria assessment; Guideline development